THE IMPLEMENTATION OF SPEECH ACTS IN OCCUPATIONAL SAFETY AND HEALTH COURSE AT POLITEKNIK BAJA TEGAL - Ria Candra Dewi; Koesumaningrum, Ismi (UNIVERSITAS PGRI YOGYAKARTA, 2024)
This study aims to analyze speech acts in the learning process of the Occupational Safety and Health course at Politeknik Baja Tegal. The study focuses on three types of speech acts: locutionary, illocutionary, and perlocutionary acts, which are used by lecturers and students in classroom interactions. Data were collected through direct observation, in-depth interviews, and video recordings during the learning process. The findings show that illocutionary acts are frequently used by lecturers to give warnings, advice, and motivation to students, which have an impact on raising their awareness of the importance of occupational safety. Perlocutionary acts also play a role in encouraging students to better adhere to safety procedures. This study offers recommendations to maximize the use of speech acts in occupational safety and health education.